ANALISIS YURIDIS TENTANG PEMBELIAN KEMBALI (BUYBACK) SAHAM TANPA PERSETUJUAN RAPAT UMUM PEMEGANG SAHAM (RUPS) (Studi Peraturan OJK Nomor 2/POJK.04/2013 tentang Pembelian Kembali Saham yang Dikeluarkan oleh Emiten atau Perusahaan Publik dalam Kondisi Pasa - Chairiyah Ella Sari Siregar; Bismar Nasution; Mahmul Siregar; Suhaidi Suhaidi (USU LAW JOURNAL, 2018)
ABSTRACT In recent years, the Indonesian economy has shown difficulties as a result of the global economic crisis marked by declining stock prices of publicly traded companies. In response, The Financial Services Authority (OJK) has re-enacted Rule Number 2 / POJK.04 / 2013 concerning Buyback of Shares Issued by Issuers or Public Companies in Significant Market Fluctuation Conditions. With this regulation, companies whose share prices tend to decline significantly are allowed to buyback without having to hold a GMS in advance. By using the methods of normative legal research, this research will examine how the arrangements are based on the Company Law and the POJK in detail, then how exactly the GMS position is in the Shareholders of the Public Company in UUPT and POJK, and how the legal protections can be provided to the POJK related Public and Investor Company. Therefore requires special regulation as the implementing regulation which accomodated by Rule Number XI.B.2 intended for the holding of buyback when the market condition is normal, and POJK No. 2 / POJK.04 / 2013 which used if the market situation tends to fluctuate significantly as a result of the crisis. Furthermore, the position of the GMS in share buyback corporate action is abolished because the company needs to take efficient measures to make an urgent decision for the company. The abolition of such GMS pursuant to Article 4 of the POJK is replaced with an announcement containing the plan, proforma, methods, and analysis of the company's management regarding the influence of share buyback on business activities and growth of the company. Concerning the concept of legal protection against investors is not sufficiently regulated in the POJK because it has been regulated comprehensively in the OJK Regulation Number 1 / POJK.07 / 2013 on Consumer Protection of Financial Services Sector, thus the form of protection stipulated in the POJK is solely for issuers / public companies only. Keyword : buyback, general meeting of shareholders, The Financial Services Authority (OJK)